Comparative Study of the Thermal Holding Capacity of Some Current Building Materials in BENIN. - PRODJINONTO, Vincent; GODONOU, Oscar; TOUKOUROU, CHAKIROU A.; VIANOU, COKOU ANTOINE (My University, 2016)
The importance and the quality of the buildings, represent an index of development of a country. We attend so more and more in our countries and particularly in Benin, an unrestrained research for improvement of the energy performances of the building. Our work enter within this scope. It seeks the improvement of the quality of the envelope of the as well as possible being opposed building through materials, with the variations in external temperature i.e. having a great thermal holding capacity. This holding capacity is characterized by damping, dephasing, heat capacity and coefficient of transmission. During our study, four materials: composite cement and fibres of ronier, composite cement and rice balls, agglomerate and composite cement and ground of bar, were designed under the same conditions and according to same mixture. They were then subjected simultaneously to solar flow during four days. From the data of flow and temperatures collected as well as modeling of a semi-infinite medium, we succeeded in estimating then to compare their holding capacities. The classification of materials by descending order of holding capacity is: composite cement and rice balls, composite cement and fibres of ronier, composite cement and ground of bar and agglomerate.
Keywords: Fibre of ronier; rice ball; agglomerate; ground of bar; damping; dephasing; coefficient of transmission; heat capacity.